2013
DOI: 10.1093/infdis/jit201
|View full text |Cite
|
Sign up to set email alerts
|

National Surveillance Data on the Epidemiology of Cholera in Kenya, 1997–2010

Abstract: Kenya has experienced substantial amounts of reported cases of cholera during the past 14 years. Recent decreases in cholera case counts may reflect cholera control measures put in place by the National Ministry of Health; confirmation of this theory will require ongoing surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 11 publications
6
29
0
Order By: Relevance
“…In general, the country has endured cross-border outbreaks coming from Nigeria The quality of cholera case management significantly depends on CFR, an important indicator that demonstrates the success or not of various strategies developed against a given cholera outbreak (14). Considering the years under review, the cholera CFR in Niger remains far higher than the 1% considered by the WHO as a standard upper limit (15,16), and CFRs also varied considerably from outbreak to outbreak. An underestimation of the actual rate of deaths during outbreaks could be strongly hypothesized to be due to the timid reporting of cases and or deaths to the DSRE then the ministry.…”
Section: Discussionmentioning
confidence: 91%
“…In general, the country has endured cross-border outbreaks coming from Nigeria The quality of cholera case management significantly depends on CFR, an important indicator that demonstrates the success or not of various strategies developed against a given cholera outbreak (14). Considering the years under review, the cholera CFR in Niger remains far higher than the 1% considered by the WHO as a standard upper limit (15,16), and CFRs also varied considerably from outbreak to outbreak. An underestimation of the actual rate of deaths during outbreaks could be strongly hypothesized to be due to the timid reporting of cases and or deaths to the DSRE then the ministry.…”
Section: Discussionmentioning
confidence: 91%
“…Stoltzfus et al [ 27 ] while looking at the interaction between climatic, environmental, and demographic factors on cholera outbreaks in Kenya found that flooding was associated with an increased risk of cholera. In an article describing the trend of cholera outbreak in Kenya, Mutonga et al [ 28 ] report that the largest outbreak occurred during the 1997 El Niño rains that caused massive flooding, with 17, 200 cases (annual incidence, 60.7 cases per 100,000 population) and an estimated 555 deaths (CFR, 3.2%). This trend continued throughout 1998.…”
Section: Resultsmentioning
confidence: 99%
“…This was in agreement with previous reports in the country. 4,17,32 Serotype Ogawa re-emerged in 2010 and replaced serotype Inaba in the 2015-2017 cholera outbreaks. The serotype switching from O1 Ogawa to Inaba and vice versa is common in many cholera-endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…3 Between 1997 to 2010, a total of 68,522 clinically suspected cases of cholera and 2,641 deaths were reported (CFR = 3.9%). 4 In 2005, a total of 990 cases and 25 deaths (CFR = 2.5%) were reported in five distinct outbreaks, including 186 laboratory-confirmed cases. 5 Between January 2015 to January 2016, a total of 11,033 cases were reported with 178 deaths (CFR = 1.6%) in 22 of 47 counties.…”
Section: Introductionmentioning
confidence: 99%